Endoscopy-assisted high anterior cervical approach in craniovertebral junction (CVJ) - Li, Pengfei; Wang, Kaixuan; Ji, Hongming; Zhang, Gangli; Chen, Shengli; Zhang, Shiyuan; Dunn, Ian F.; Hu, Changchen (Frontiers in Surgery, 2022)
Background Surgical procedures in the craniovertebral junction (CVJ) suffer from specific challenges due to the proximity between the cranium and spine containing the critical neurovascular structures and the brainstem, respectively. Owing to the complex transitional zone, it is highly challenging for classic surgical approaches to practically acquire the additional exposure to neurovascular structures of the CVJ. Inspired by these facts, we explore the feasibility of an endoscopy-assisted high anterior cervical approach in the CVJ. Methods To explore the feasibility of an endoscopy-assisted approach, we quantitatively assessed the surgical corridor and extent of exposure of the CVJ in 6 cadaveric specimens using 0° and 30° endoscopes. Results The applied endoscopes provided adequate exposure to neurovascular structures and the brainstem in the CVJ. Notably, the resection of the anterior arch of C1 is avoided in minimal anterior clivectomy. Further, improved exposure of the CVJ is obtained after removing the odontoid. Conclusion An endoscope-assisted high anterior cervical approach in the CVJ significantly preserved the cervical spine stability while minimalizing the risk of neurovascular injury within the surgical corridor.